Cardiac magnetic resonance feature tracking in Kawasaki disease convalescence - Konstantinos Bratis; Pauline Hachmann; Nicholas Child; Thomas Krasemann; Tarique Hussain; Sophie Mavrogeni; Rene Botnar; Reza Razavi; Gerald Greil (Wolters Kluwer Medknow Publications, 2017)
Objective: The objective of this study was to determine whether left ventricular (LV) myocardial deformation indices can detect subclinical abnormalities in Kawasaki disease convalescence. We hypothesized that subclinical myocardial abnormalities due to inflammation represent an early manifestation of the disease that persists in convalescence. Background: Myocardial inflammation has been described as a global finding in the acute phase of Kawasaki disease. Despite normal systolic function by routine functional measurements, reduced longitudinal strain and strain rate have been detected by echocardiography in the acute phase. Methods and Results: Peak systolic LV myocardial longitudinal, radial, and circumferential strain and strain rate were examined in 29 Kawasaki disease convalescent patients (15 males; mean [standard deviation] age: 11 [6.6] years; median interval from disease onset: 5.8 [5.4] years) and 10 healthy volunteers (5 males; mean age: 14 [3.8] years) with the use of cardiac magnetic resonance (CMR) feature tracking. Routine indices of LV systolic function were normal in both groups. Comparisons were made between normal controls and (i) the entire Kawasaki disease group, (ii) Kawasaki disease subgroup divided by coronary artery involvement. Average longitudinal and circumferential strain at all levels was lower in patients compared to normal controls. In subgroup analysis, both Kawasaki disease patients with and without a history of coronary involvement had similar longitudinal and circumferential strain at all levels and lower when compared to controls. There were lower circumferential and longitudinal values in Kawasaki disease patients with persisting coronary artery lesions when compared to those with regressed ones. Conclusion: In this CMR study in Kawasaki disease convalescent patients with preserved routine functional indices, we detected lower circumferential and longitudinal strain values compared to normal controls, irrespective of the coronary artery status.